2012
DOI: 10.1177/0961000611434757
|View full text |Cite
|
Sign up to set email alerts
|

Library subject guides: A case study of evidence-informed library development

Abstract: Abstract:This paper describes the process whereby a University Library investigated the value of its subject guides to its users. A literature review and surveys of library staff, library users and other libraries were carried out. Existing library subject guides and those of other higher education libraries were evaluated. . It now has four main sites and over 25,000 students, many of whom are part-time or studying at a distance from the University. Subject guides are seen as one of the ways that the library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
7
0
3
Order By: Relevance
“…The researchers do not just rely on Web usage statistics but also on student and librarian feedback to see whether students found the guides useful and what design practices improve use. Their conclusions add to the growing body of research about patron use of guides embedded in course pages (Wakeham, Roberts, Shelley, & Wells, 2012;Chiware, 2014).…”
Section: Commentarymentioning
confidence: 60%
“…The researchers do not just rely on Web usage statistics but also on student and librarian feedback to see whether students found the guides useful and what design practices improve use. Their conclusions add to the growing body of research about patron use of guides embedded in course pages (Wakeham, Roberts, Shelley, & Wells, 2012;Chiware, 2014).…”
Section: Commentarymentioning
confidence: 60%
“…Research around the utilization of library guides has identified that when library guides are used, these guides do improve research skills, GPA and retention (May & Leighton, 2013;Wakeham, Roberts, Shelley, & Wells, 2012). However, most utilization studies have focused on how the library guides are built and embedded (May & Leighton, 2013;Wakeham, Roberts, Shelley, & Wells, 2012), and not on how student perception of the guide may relate to student decisions to use the resources.…”
Section: Using Guidesmentioning
confidence: 99%
“…La forma que adoptan estas guías es generalmente la de una página web o la de un documento en pdf, aunque también es posible utilizar las tecnologías de la Web 2.0, como pueden ser las wikis o el uso de Delicious (WAKEHAM et al, 2012;MORRIS;DEL BOSQUE, 2010), o su adaptación a dispositivos móviles o a formatos audiovisuales (STRUTIN, 2008). También existe software específico, como Libguides 4 , que son sistemas de gestión de contenidos, que permiten la creación y personalización de guías temáticas en un entorno web.…”
Section: Guías Temáticasunclassified
“…Su uso es considerable y la valoración por parte de los usuarios es en general positiva (COURTOIS; HIGGINS; KAPUR, 2003;WAKEHAM et al, 2012). Además tiene un efecto positivo en las personas que las usan, ya que, como observó Galvin (2005), los estudiantes que hacen uso de las guías temáticas tienden a utilizar más recursos académicos.…”
Section: Guías Temáticasunclassified
See 1 more Smart Citation